Structural properties and adsorption capacities of Mesona chinensis Benth residues dietary fiber prepared by cellulase treatment assisted by Aspergillus niger or Trichoderma reesei. (1st May 2023) - Si, Jingyu; Yang, Chaoran; Chen, Yi; Xie, Jianhua; Tian, Shenglan; Cheng, Yanan; Hu, Xiaobo; Yu, Qiang
Highlights: The five biological methods were used to prepare soluble dietary fiber (SDF). The highest SDF yield was obtained by Aspergillus niger -enzyme hydrolysis. The SDF with porous structure was found by Aspergillus niger treatment. Aspergillus niger -enzyme hydrolysis improved hypoglycemic ability of SDF. The SDF showed highest nitrite binding capacity by Aspergillus niger treatment. Abstract: The effects of enzyme hydrolysis treatment, Aspergillus niger fermentation treatment, Trichoderma reesei fermentation treatment, Aspergillus niger -enzyme hydrolysis treatment and Trichoderma reesei -enzyme hydrolysis treatment on structural properties and adsorption capacities of soluble dietary fiber from Mesona chinensis Benth residues were evaluated and compared. The Aspergillus niger -enzyme hydrolysis treatment sample possessed more diverse structure, lower crystallinity and thermal stability than other modified samples. Meanwhile, it also observed the highest soluble dietary fiber yield (20.76 ± 0.31 %), water-holding capacity and glucose adsorption capacity (38.03 ± 0.28 mg/g). The Aspergillus niger fermentation treatment sample generated a high oil-holding capacity, nitrite ion adsorption capacity (181.84 ± 6.67 ug/g), cholesterol adsorption capacity (16.40 ± 0.37 mg/g) and sodium cholate adsorption capacity (94.80 ± 1.41 mg/g). Additionally, different monosaccharide composition was exhibited due to diverse extraction methods. Our finding revealed that these two modification methods could effectively enhance the economic value of Mesona chinensis Benth residues.